2023
DOI: 10.1038/s41408-022-00779-2
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and outcomes of frail older adults in clinical trials in multiple myeloma: A systematic review

Abstract: Multiple myeloma (MM) is an incurable blood cancer that primarily affects older adults. Several frailty tools have been developed to address the heterogeneity of aging in this population. Uptake of these measures has been variable, leading to a gap in knowledge regarding the proportion of enrolled trial participants considered frail and uncertainty in the treatment-related effects and outcomes among this high-risk population. We performed a systematic review of therapeutic interventional MM clinical trials rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…While the incorporation of frailty at any time point represents an important step in the evaluation of a patient, there is a paucity of data examining the longitudinal evaluation of frailty. To our knowledge, there is only one previously published therapeutic clinical trial (VBDD-VERRUM) and there are three ongoing studies evaluating how frailty changes over time (UKMRA FiTNEss, HOVON 123, HOVON 143) [ 8 ]. As compared to clinical trials, there is even less data in the real-world evaluating frailty over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the incorporation of frailty at any time point represents an important step in the evaluation of a patient, there is a paucity of data examining the longitudinal evaluation of frailty. To our knowledge, there is only one previously published therapeutic clinical trial (VBDD-VERRUM) and there are three ongoing studies evaluating how frailty changes over time (UKMRA FiTNEss, HOVON 123, HOVON 143) [ 8 ]. As compared to clinical trials, there is even less data in the real-world evaluating frailty over time.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study only evaluated frailty longitudinally among newly-diagnosed patients, frailty re-assessment at the time of each MM relapse may be particularly important. Several post-hoc analysis of recently conducted clinical trials in MM have demonstrated the prognostic value of frailty assessments in both newly-diagnosed and relapsed/refractory settings, even when retrospectively derived using the simplified frailty scale (modified IMWG frailty scale) [ 8 ]. Although, compared to the fit patients, patients who were more frail had poorer outcomes in these relapsed trials, many of these analyses were done only at a single time point and therefore additional studies are required to further understand the longitudinal trajectory of frailty in both the newly-diagnosed as well as the relapsed/refractory setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple myeloma (MM), the second most common blood cancer, is a plasma cell malignancy frequently accompanied by hypercalcemia, immune dysfunction, and renal failure [ [1] , [2] , [3] ]. Despite the employment of various therapeutic methods, such as immunomodulatory agents, proteasome inhibitors, and autologous stem cell transplantation (ASCT), MM remains an incurable disease with nearly 160,000 new cases and 106,000 deaths annually [ 4 , 5 ]. Unfortunately, relapse and drug resistance continue to pose significant challenges in the management of MM [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferrara et al proposed definitions for lack of fitness for both intensive and non‐intensive chemotherapy 28 . Studies have historically been poor at enrolling elderly patients due to restrictive inclusion criteria, but this is now improving, 29–51 with the development of several guidelines and best practice papers focussing on the optimal care of older patients with malignancy 28,52–67 . The boundary between frailty and disease can be difficult to delineate, and this is an additional complicating factor when planning treatment for patients 5,68,69 .…”
Section: Introductionmentioning
confidence: 99%